Perceptions of local community and visitors and their willingness to pay for firefly conservation in Kuala Selangor, Malaysia - Rosli, Nadirah (2021)
Fireflies are a type of insect from the family Lampyridae and order Coleoptera. It has the unique feature of producing light from its lower abdomen. Fireflies are an ecotourism icon for the Kuala Selangor district and firefly watching activities have been operating since 1980 in Kampung Kuantan Firefly Park (KKFP). The presence of fireflies in KKFP has given many benefits to the local communities in terms of economic, social, and cultural benefits. However, the population of fireflies has decreased by 42% since 2007 and this can be seen from the current number of fireflies of 400 compared to 600 individuals previously on each Berembang tree. This event occurred as a result of various factors, including habitat destruction, artificial light, use of pesticides, and conversion of land use to oil palm plantations and shrimp ponds. Various efforts to conserve fireflies and their habitats have been done and this study also would contribute to the conservation efforts of fireflies from the aspect of economic valuation. This study aimed to identify the awareness, perception, and attitude of respondents towards the conservation of fireflies. Respondents would express their views by choosing one of the five interval scales for the given statement. In addition, this study also identified factors that influence the Willingness to Pay (WTP) for the conservation of fireflies in Kuala Selangor by using the Contingent Valuation Method (CVM). The Double Bounded Dichotomous Choice (DBDC) format is a method that offers the starting bid value to the respondents. A total of 730 (330 visitors and 400 locals) were selected using convenience and stratified random sampling techniques. The results revealed that the level of awareness of the respondents was moderate and had a positive perception and attitude towards the conservation of fireflies in Kuala Selangor. The study also found that the factors that influenced the WTP for visitors include bid value, age, household’s number, monthly income, awareness, attitude, and perception. The WTP for locals is influenced by bid value, gender, awareness, and attitude. The study found that the means WTP for visitors of RM12.93 was higher than local community and RM12.43 per individual per year for firefly conservation. The total economic value for the conservation of fireflies and their habitat in Kuala Selangor was estimated at RM741, 768.24 visitors, lower compared to the local community at RM2, 338, 083. The findings on the economic value of this study is useful because it serves as a guideline for policymakers and the Kuala Selangor District Council to develop a sustainable conservation plan for the protection of these natural resources in the long run.